Penerapan Metode WMA dan EOQ pada Sistem Informasi Pengendalian Persediaan Stok Obat di Apotek Damhil - Padiku, Indhitya; Lillyan Hadjaratie; Dizky Ramadani Putri Papeo; Muh. Fikri F. Walahe (Jurnal Teknik, 2023)
Damhil UNG Pharmacy is one of the pharmacies in Gorontalo City whose inventory management is still difficult because preparation takes a long time by recording and checking what drugs are running out. In addition to reporting problems, the amount of stock added often exceeds the number of requests (Overstock) and often less than the number of requests (Stockout). As a result, making customers or consumers lost and profits are decreasing. A method is needed to overcome these problems. The methods that can be used are the Weighted Moving Average (WMA) and Economic Order Quantity (EOQ) forecasting methods applied to the drug stock inventory control information system. This information system is based on a website developed using the prototype method. The result obtained is the preparation of drug inventory reports and drug needs in the future more effective and better.